The Role and Position of the Macroeconomic Environment on the Revenues of Tehran Municipality - Mahdi Yazdani; Alireza Basiri (اقتصاد شهری, 2023)
The financing of municipalities as local governments is one of the most important and challenging issues of the urban economy in developing and developed countries, where this issue is more important in the case of the capital of the countries. The city of Tehran, as one of the capitals, is not an exception to this matter, and the financing of its investment projects was very important in different years especially in the last decade, when Iran's economy was faced with important and serious challenges in the macroeconomic and international environment. Moreover, although municipalities, such as Tehran municipality, have tried to diversify and stabilize their income flows, the important point is that macroeconomic conditions can play a significant role in this regard. This study tries to evaluate the effects of macroeconomic stability shocks on the financing of investment projects in Tehran. For this purpose, a vector autoregressive model was used from 1991 to 2021 and was evaluated and compared the response of two municipal revenue components including a) the revenues from public duties and the financing from the capital and financial assets as the most important and stable components, and b) the other revenue components to macroeconomic stability shocks. The results show that the financing of investment projects in Tehran has shown a significant reaction to the shocks of macroeconomic variables, and on the other hand, the shock of the macroeconomic stability causes the resources from the financing of capital and financial assets for the city's investment projects to have a negative reaction to this shock. Based on this, policymakers and annual budget regulators should pay enough attention to these results. JEL Classification: C22, C32, R38, R51.